1988
DOI: 10.1002/art.1780310802
|View full text |Cite
|
Sign up to set email alerts
|

Synovial microenvironment‐t cell interactions

Abstract: Synovitis in rheumatoid arthritis is characterized by infiltration of the synovium by T and B lymphocytes and monocytes, as well as by the proliferation of synovial lining cells, fibroblasts, and endothelial cells. To study synovial cell‐T cell interactions in vitro, we established cultures of fibroblast‐like synovial cells, and used these cells in a synovial cell‐T cell binding assay. Using T cells at various stages of differentiation and activation, we found that human thymocytes and mitogen‐activated periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…In vitro studies revealed that human T cells have the ability to adhere to synoviocytes as well as to dermal fibroblasts via CD2/CD58 (LFA-3) and LFA-1 (CD11a/CD18)/CD54 (ICAM-1) interactions (12,13,49). Furthermore, the cellular adhesion between T cells and synoviocytes induces the production of IL-1␤ by synovial cells in part through LFA-1-ICAM-1 interaction (17).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies revealed that human T cells have the ability to adhere to synoviocytes as well as to dermal fibroblasts via CD2/CD58 (LFA-3) and LFA-1 (CD11a/CD18)/CD54 (ICAM-1) interactions (12,13,49). Furthermore, the cellular adhesion between T cells and synoviocytes induces the production of IL-1␤ by synovial cells in part through LFA-1-ICAM-1 interaction (17).…”
Section: Discussionmentioning
confidence: 99%
“…B-lymphocytes can be activated not only by various cytokines but also by direct interactions with T-lymphocytes via TCR/MHC class 11 and gp39/CD40 interactions (Noell et al, 1992;laneway and Trevers, 1994). On the other hand, several lines of evidence have demonstrated that the interaction of lymphocytes with other cell types is also an important component of inflammatory responses and is essential in a number of other contact-mediated processes, such as lymphopoiesis and lymphocyte homing and migration (Dustin and Springer, 1988;Haynes et al, 1988;Denning et al, 1989;Berg et al, 1991;van Ewi jk, 1991;Kincade et al, 1993;De Boer et al, 1994;Downey, 1994).…”
Section: Do Lymphocytes Interact Withmentioning
confidence: 99%
“…Piela and Korn (1990) reported that the increased adhesion between IFN-y-stimulated dermal fibroblast and resting T-lymphocytes was inhibited by mAb to ICAM-1 or LFA-1 and concluded that the ICAM-1/LFA-l pathway plays a major role in their system. Alternatively, it was proposed that T-lymphocyte adhesion to human synovial fibroblasts resulted in cellular retention in the inflamed synovium (Haynes et al, 1988;Krzesicki et al, 1991 (Murakami et al, 1993a,b). VLA integrins are members of the 11 subfamily, and each contains the 11 subunit in association with one of at least six distinct (x subunits (Hemler, 1990 (Murakami et al, 1993a).…”
Section: (3) Interaction With Endothelial Cellsmentioning
confidence: 99%
“…Isolation and activation of T lymphocytes Thymocytes were teased from thymus obtained from four control rats, aged 3-5 months, and were purified as described [14]. Activated T lymphocytes were prepared by the incubation of thymocytes with RPMI 1640 medium (GIBCO) supplemented with 10% fetal calf serum (FCS) and 20 pg/ml concanavalin A (Con A; Sigma) for 3 days, and were then washed with 0 3 M amethylmannoside (Sigma) to remove residual Con A [14].…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…Activated T lymphocytes were prepared by the incubation of thymocytes with RPMI 1640 medium (GIBCO) supplemented with 10% fetal calf serum (FCS) and 20 pg/ml concanavalin A (Con A; Sigma) for 3 days, and were then washed with 0 3 M amethylmannoside (Sigma) to remove residual Con A [14]. Activated T lymphocytes were selected using plastic surfaces coated with anti-CD8 antibodies [15].…”
Section: Phagocytosis Assaymentioning
confidence: 99%